Spiritual impact of theocentric outdoor environmental education on affective disposition among Malaysian pre-service science teachers - Shaharil, Najwa Huda; Syed-Abdullah, Sharifah Intan Sharina; Mohd Fakhruddin, Fathiyah; Abd Rahman, Norshariani; Ramlan, Mohd Aswad (Wise Academia Research Solutions, 2024)
This study utilizes theocentric outdoor environmental education (TOEE) approach in a one-day program for 20 pre-service science teachers to explore how the spirituality aspects in TOEE approach impacts participants' environmental affective disposition. Participants’ experiences in the program were interpreted through photo elicitation focus group discussions. The findings suggest that the TOEE approach nurtures environmental disposition among pre-service science teachers. TOEE approach enhances aspects of environmental disposition in three key ways: (i) by fostering environmental sensitivity through a profound sense of reverence and gratitude for nature as a divine creation; (ii) by instilling a sense of personal responsibility through the recognition of one's role as khalifah or steward on Earth; and (iii) by motivating individuals through the belief in divine rewards and punishments, which encourages pro-environmental actions and discourages environmental harm. The insights serve as a practical strategy for enhancing the current sustainability curriculum to better fit the Malaysian religious context.